A Study of Magnetic Amplifier-based Power Flow Controller for Power System Stability Improvement. Issue 9 (27th May 2016) - Lin, Keman; Tomsovic, Kevin; Wan, Qiulan; Dimitrovski, Aleksandar
Abstract: This article presents a magnetic amplifier-based power flow controller as a new approach to control power flow based on a magnetically saturated reactor concept. The magnetic amplifier-based power flow controller uses the magnetic field as control medium to decrease the operating energy losses and increase system reliability. By providing continuous impedance, the magnetic amplifier-based power flow controller can suppress the inter-area oscillation and improve the system stability. A model of magnetic amplifier-based power flow controller is built and verified by lab experiments. A control strategy implementing the magnetic amplifier-based power flow controller is proposed to demonstrate the application of this new device to damp low-frequency oscillation in an interconnected power system. A comparative analysis of the controller's performance is carried out and incorporated with various input signals and multiple loading conditions. The simulations are conducted by power systems CAD (PSCAD, Manitoba Hydro International Ltd., Winnipeg, Canada). The results show the effectiveness of the controller in damping inter-area oscillations.